Proses Penyelesaian Diversi terhadap Anak yang Berkonflik dengan Hukum di Pengadilan Negeri Bukittinggi kelas IB - Welly Oktrisni (Pusat Riset dan Inovasi Nasional, 2026)
Efforts to protect children in conflict with the law constitute a concrete manifestation of the state’s responsibility in implementing the principles of restorative justice. This study aims to comprehensively examine the implementation process of diversion at the Pengadilan Negeri Bukittinggi and to assess the extent to which its application achieves the primary objective of the juvenile criminal justice system, namely restoring the child’s social condition without emphasizing retribution. This research employs an empirical juridical approach by combining literature review and field research through interviews with judges, court clerks, and other relevant parties. The findings indicate that the implementation of diversion at the Pengadilan Negeri Bukittinggi has been carried out in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The diversion process is conducted through deliberation involving the offender, the victim, their respective families, and supporting institutions under the guidance of a diversion facilitator. However, several challenges remain, including limited public understanding of the importance of restorative-based settlement, insufficient human resources with adequate competence in implementing diversion, and frequent failures in reaching agreements between offenders and victims. This study concludes that diversion in court proceedings is not merely a legal obligation but also an essential instrument in creating a more humane child-oriented justice system. Therefore, enhancing the competence of law enforcement officers and strengthening inter-agency coordination are necessary to support the sustainable success of diversion.